Holiday rentals: the new gentrification battlefront - Cocola-Gant, Agustín (2018)
In this paper, I explore the impacts of holiday rentals in the historic centre of Barcelona. The intention is to contribute towards a conceptualisation of this unexplored phenomenon with the aim of better understanding why it represents the new gentrification battlefront in several tourist destinations. I suggest that the rhetoric of the sharing economy conceals the fact that holiday rentals are actually a new business opportunity for investors, tourist companies and individual landlords and, for this reason, long-term residents represent a barrier to capital accumulation. I show that there is an increasing conversion of housing into accommodation for visitors and that such conversion involves different forms of displacement. Importantly, when residents move out, the only buyers tend to be tourist investors. In such a context, I suggest that the growth of vacation flats produces conditions that solely enable the reproduction of further accommodation for visitors, rather than for long-term residential use. I call this process 'collective displacement', that is to say, a substitution of residential life by tourism. Ultimately, throughout this paper I suggest the importance of undertaking critical research relevant to those experiencing urban inequalities. Documenting and producing data about the way in which displacement takes place can be a crucial political tool for those who are fighting for staying put.